Effect of Customer Experience Quality on Loyalty in Fitness Services - Eskiler Ersin; Safak Furkan (Sciendo, 2022)
Customer experience quality is an important and relatively new concept for service businesses in gaining a sustainable competitive advantage. Although the literature on customer experience quality is expanding, there is a gap concerning the antecedent and consequences of customer experience in fitness services. In this context, we tested a model that explains the precursors and implications of customer experience quality in the context of fitness services. This study was based on a non-experimental, depictive, and descriptive design. Within the scope of this study, 287 participants (216 male, 71 female) selected through a convenience sampling technique applied a self-administered questionnaire. Data were analyzed through confirmatory factor analysis and a structural equation model. The findings show that service result quality, customer-employee interaction quality, and customer-customer interaction quality affect customer experience quality, which in turn affects customer loyalty. These results show that improving the service outcome quality results in customers who experience high-quality customer-employee and customer-customer interactions becoming loyal customers.